A Grass Chopping Machine: Design of Mechanism System for Mowing Grass Chopper - Cahyono, Daffa Ammar (TEKNIKA, 2023)
The purpose of making this machine is as a solution to reduce the need for cattle breeders who offer chopped grass as a mixture of animal feed. And it is hoped that it can also help breeders to increase their productivity. This plan aims to explain the cutting mechanism system on a grass chopper where the final result of the grass cutting is in accordance with the exact size that the breeder wants. This grass chopper is a machine driven by a motor with a V-belt transmission system and assisted by other engine components. The main driving force for this grass chopper is a HONDA brand gasoline engine with the GX 160 H1 type, with a rotation of 3600 Rpm, and has a power of 5.5 hp, with a total weight of 15 kg. This grass chopper uses a single blade cutting method with steel material with dimensions of length 620 mm, width 45 mm and also a thickness of 2 mm, this machine uses a gasoline engine and therefore can be used anywhere, this lawn mower can later cut grass. with a production capacity of 118 Kg/hour. Keywords: grass chopper, transmission system, solidworks